Mathematical modelling on the spread of hand, foot and mouth disease (HFMD) in Sarawak - Chuo, Felix Sing Tiing. (Faculty of Computer Science and Information Technology, 2008)
Since 1997, every three years Sarawak had been experiencing outbreak of hand, foot and mouth disease (HFMD). the outbreak of HFMD in year 2006 resulted in 13 deaths with 41,423 cases reported. It also resulted in closing of all nurseries, kindergartens and primary one to primary three classes for about two weeks. Each outbreak of HFMD caused fear and anxiety in the community. The next outbreak is predicted to be in year 2009. Mathematical models have been widely used to predict and understand the dynamics of infectious disease. In this project we build a simple mathematical model to predict the spread of HFMD in Sarawak in terms og number of infected individuals per unit of time and the duration of the outbreak. Then using the model we try to determine the critical parameter that can help in curbing the spread of HFMD. We studied the clinical characteristics of HFMD.